2008
DOI: 10.1101/gad.1702708
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone signaling through low-density lipoprotein-related protein 6

Abstract: Intermittent administration of PTH stimulates bone formation, but the precise mechanisms responsible for PTH responses in osteoblasts are only incompletely understood. Here we show that binding of PTH to its receptor PTH1R induced association of LRP6, a coreceptor of Wnt, with PTH1R. The formation of the ternary complex containing PTH, PTH1R, and LRP6 promoted rapid phosphorylation of LRP6, which resulted in the recruitment of axin to LRP6, and stabilization of ␤-catenin. Activation of PKA is essential for PTH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
213
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(229 citation statements)
references
References 61 publications
13
213
1
1
Order By: Relevance
“…Alternatively, data from another in vitro study showed evidence for PTH-induced association of the PTH receptor with LRP6, leading to activation of LRP6 and canonical Wnt signaling. (71) This report raises the possibility that PTH might act directly on the Wnt signaling pathway through LRP6, irrespective of any decreases in sclerostin expression. Interestingly, two studies demonstrated a normal anabolic response to intermittent PTH in LRP5-deficient mice (LRP5 knockouts), indicating that LRP5 is not needed for intermittent PTHs stimulatory effects on bone formation.…”
Section: Osteocytes Mechanical Loading and Interface With The Pth Pmentioning
confidence: 73%
“…Alternatively, data from another in vitro study showed evidence for PTH-induced association of the PTH receptor with LRP6, leading to activation of LRP6 and canonical Wnt signaling. (71) This report raises the possibility that PTH might act directly on the Wnt signaling pathway through LRP6, irrespective of any decreases in sclerostin expression. Interestingly, two studies demonstrated a normal anabolic response to intermittent PTH in LRP5-deficient mice (LRP5 knockouts), indicating that LRP5 is not needed for intermittent PTHs stimulatory effects on bone formation.…”
Section: Osteocytes Mechanical Loading and Interface With The Pth Pmentioning
confidence: 73%
“…Intermittent but not continuous PTH has also been shown to induce b-catenin signaling by directly binding to LRP6/frizzled complex. (75) It is assumed that hyperparathyroidism is analogous to continuous PTH administration such that these findings using intermittent PTH would not be relevant in the setting of CKD. (75) In support of this, transgenic mice expressing constitutively active PTH receptors have a bone phenotype similar to osteitis fibrosa.…”
Section: Discussionmentioning
confidence: 99%
“…(75) It is assumed that hyperparathyroidism is analogous to continuous PTH administration such that these findings using intermittent PTH would not be relevant in the setting of CKD. (75) In support of this, transgenic mice expressing constitutively active PTH receptors have a bone phenotype similar to osteitis fibrosa. (74) However, it is also possible that elevations in sclerostin may contribute to repression of PTH signaling in CKD bones because PTH responses are blunted in transgenic mice overexpressing sclerostin.…”
Section: Discussionmentioning
confidence: 99%
“…9,43 It is worth mentioning that the transcriptional activity of b-catenin may also occur independent of the activation of Wnt and Fz. Activation of G protein-coupled receptors such as prostanoid (EP2, EP4), 44 lysophosphatidic acid (LPA2, LPA3), 18,45 gonadotrophin releasing hormone 46 and parathyroid 47 can also turn on b-cateninmediated gene transcriptional programs. In a recent study, it has been shown that the free G a and G bg subunits released from an activated G protein act co-operatively to inhibit b-catenin degradation and subsequently activate b-catenin-mediated transcriptional program.…”
Section: Canonical Wnt Pathwaymentioning
confidence: 99%